2001
DOI: 10.1177/001440290106800104
|View full text |Cite
|
Sign up to set email alerts
|

After Preschool Inclusion: Children's Educational Pathways over the Early School Years

Abstract: A complex array of factors influences the implementation of inclusion within educational systems. This article examines decision making regarding young children's participation in inclusive programs. A qualitative design was employed to study influential factors over the course of a 5-year period as children moved from inclusive preschool placements to elementary school. Family, classroom, school, and societal influences were examined through families' perspectives on children's school experiences. At the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 33 publications
4
52
0
6
Order By: Relevance
“…existence and severity of hearing loss, levels of academic and social competence) at this point for guidance into inclusive settings. On the other hand, the scarcity of research studies in the literature that have concluded with universal, common, and standard criteria to employ during guidance procedures should be noted (Eaves & Ho, 1997;Guardino, 2008;Hanson et al, 2001). The results from these rare studies have produced the following criteria: appropriate student profile for inclusive settings, the age when started using hearing aid technologies (when did they receive the cochlear implant), no accompanying disability, and only a moderate level of hearing loss (Archbold et al, 1998;Çerezci, 2015;Eaves & Ho, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…existence and severity of hearing loss, levels of academic and social competence) at this point for guidance into inclusive settings. On the other hand, the scarcity of research studies in the literature that have concluded with universal, common, and standard criteria to employ during guidance procedures should be noted (Eaves & Ho, 1997;Guardino, 2008;Hanson et al, 2001). The results from these rare studies have produced the following criteria: appropriate student profile for inclusive settings, the age when started using hearing aid technologies (when did they receive the cochlear implant), no accompanying disability, and only a moderate level of hearing loss (Archbold et al, 1998;Çerezci, 2015;Eaves & Ho, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The responsibilities of the guidance team are to review students' reasons for applying, to organize meetings concerning guidance into educational settings after educational assessment, and to decide on the educational-setting placement (Strickland & Turnbull, 1993). Hanson et al's (2001) study, which was designed to determine the opinions of parents whose children with hearing loss had been placed within inclusive preschool settings about the process of deciding which educational setting their child would take part in during their primary education years, is one of the studies focusing on guidance procedures in the international literature. They concluded parents, experts, non-governmental organizations, the physical structure of schools, the presence of support services, the attitudes of normally hearing peers, and teachers' professional background/capabilities to affect the placement decision.…”
mentioning
confidence: 99%
“…Il s'agit notamment des attitudes négatives des principales parties prenantes (Wolery, Brookfield, Huffman, Schroeder, Martin, Venn et Holcombe, 1993;Bricker, 1995), de ratios personnel-enfants trop bas 79 volume XXXIX:2, automne 2011 www.acelf.ca et de l'insuffisance de personnel de soutien (Wolery et al, 1993), du manque de places disponibles (Hanson et al, 2001), de l'accès limité aux ressources et à de l'équipement adapté ainsi que du manque de formation adéquate du personnel (Buysse, Wesley, Keyes et Bailey, 1996;Spivak et al, 2002;Praisner, 2003). Le type et la gravité du handicap peuvent aussi influer sur la probabilité qu'un enfant soit inclus dans un service de garde.…”
Section: Des Obstacles à Surmonter Pour Des Pratiques Efficacesunclassified
“…Other factors that contributed to academic failure in regards to teachers were: not individualizing to meet students needs, overusing instruction instructional assistants, underestimating the effectiveness of explicit instruction and assuming that sitting quietly is an appropriate alternative to participation. Hanson, et al, (2001) state co-teaching should enhance the classroom environment by blending the area of expertise between two professionals. As the two teachers interact, students should gain new perspectives on content and expose themselves to different ways of expressing ideas.…”
Section: Negative Academic Outcomesmentioning
confidence: 99%